The Optimization Paths of China’s International Commercial Arbitration Interim Measures System - ., MengXin; Radzi, Mohd Shahril Nizam Md (Journal of Ecohumanism, 2025)
As globalization gains momentum, international commercial arbitration has emerged as a pivotal mechanism for addressing cross-border commercial conflicts. Interim measures, integral to the arbitration process, serve to safeguard the interests of parties and mitigate potential harm during disputes. Yet, China's system of interim measures within international commercial arbitration exhibits certain shortcomings, particularly concerning the application and enforcement of legal provisions, necessitating further refinement. This paper, grounded in the context of interim measures in international commercial arbitration, examines the fundamental functions and current application of these systems. It also scrutinizes the legislative and practical challenges China faces in this domain. Drawing from the experiences of other jurisdictions, the author offers preliminary insights into enhancing China's relevant systems, thereby contributing to the ongoing development of international commercial arbitration in the country.